Alternative Pathways of IL-1 Activation, and Its Role in Health and Disease - Pyrillou, Katerina; Burzynski, Laura C.; Clarke, Murray C. H. (Frontiers in Immunology, 2020)
Cytokines activate or inhibit immune cell behaviour and are thus integral to all immune responses. IL-1α and IL-1β are powerful apical cytokines that instigate multiple downstream processes to affect both innate and adaptive immunity. Multiple studies show that IL-1β is typically activated in macrophages after inflammasome sensing of infection or danger, leading to caspase-1 processing of IL-1β and its release. However, many alternative mechanisms activate IL-1α and IL-1β in atypical cell types, and IL-1 function is also important for homeostatic processes that maintain a physiological state. This review focuses on the uncommon, yet arguably more interesting biology of IL-1. We detail the production by, and effects of IL-1 on specific innate and adaptive immune cells, report how IL-1 is required for barrier function at multiple sites, and discuss how perturbation of IL-1 pathways can drive disease. Thus, although IL-1 is primarily studied for driving inflammation after release from macrophages, it is clear that it has a multifaceted role that extends far beyond this, with various unconventional effects of IL-1 vital for health. However, much is still unknown, and a detailed understanding of cell-type and context-dependent actions of IL-1 is required to truly understand this enigmatic cytokine, and safely deploy therapeutics for the betterment of human health.